Biomonitoring gozdnega ekosistema v imisijskem območju Termoelektrarne Šoštanj - Al Sayegh-Petkovšek, Samar (Zbornik gozdarstva in lesarstva, 2006)
The aim of the long standing forest ecosystem research was to asses the physiological state of Norway spruce (Picea abies (L.) Karst.) on the basis ofthe needle biochemical parameters in the area infl uenced by sulphur emissions from the Šoštanj Thermal Power Plant (ŠTPP). The total sulphur content, photosynthetic pigments, ascorbic acid (vitamin C) and f -tocopherol(vitamin E) were analysed in current and one year old needles from the seventh whorl from the top in fi ve 60-100 year old spruce trees in autumn every year; the results of current needles are presented in this paper. Ten differently polluted sampling plots were selected in profile: Lajše, Topolšica, Laze, Veliki Vrh, Graška gora, Zavodnje, Brneško sedlo, Kramarica, Kope and Smrekovec. Dominant air pollutants were sulphur dioxides,nitrogen oxides and ozone. Results show that the condition of Norway spruce has improved since 1995 and particularly since 2000 due to installation of desulphurization devices on Units 4 and 5 of the TPPŠ, part ofunexplained fl uctuations in investigated parameters are most probably consequences of variations in climatic conditions.
Keywords: biomonitoring; onesnaženje; Picea abies; Slovenija; smreka; termoelektrarna Šoštanj